2014
DOI: 10.1038/ncomms5587
|View full text |Cite
|
Sign up to set email alerts
|

Tension on the linker gates the ATP-dependent release of dynein from microtubules

Abstract: Cytoplasmic dynein is a dimeric motor that transports intracellular cargoes towards the minus-end of microtubules (MTs). In contrast to other processive motors, stepping of the dynein motor domains (heads) is not precisely coordinated. Therefore, the mechanism of dynein processivity remains unclear. Here, by engineering the mechanical and catalytic properties of the motor, we show that dynein processivity minimally requires a single active head and a second inert MT binding domain. Processivity arises from a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
142
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(167 citation statements)
references
References 51 publications
(119 reference statements)
19
142
0
Order By: Relevance
“…Our results are consistent with our own (11) and others' reports (12,13,20) that less force is required to break the dynein-MT bond when pulling the motor forward than backward. Interestingly, in the apo state, whether tension is applied via the linker vs. the C terminus has little effect on unbinding forces, implying that linker conformation and/or tension transmitted through the dynein ring are not responsible for the anisotropy.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Our results are consistent with our own (11) and others' reports (12,13,20) that less force is required to break the dynein-MT bond when pulling the motor forward than backward. Interestingly, in the apo state, whether tension is applied via the linker vs. the C terminus has little effect on unbinding forces, implying that linker conformation and/or tension transmitted through the dynein ring are not responsible for the anisotropy.…”
Section: Discussionsupporting
confidence: 83%
“…Under backward load, catch bonding (diminished unbinding rate with applied force) has been reported (31-33), but we instead found that slip bonding occurs up to ∼2 pN, above which the unbinding rate is insensitive to force (Fig. 1 F and G), characteristic of ideal bonding (these findings agree with those from constant-force assays (20) that directly measure unbinding rates). Because the behavior seen here under rearward force exhibits features of both slip bonding (at low force) and ideal bonding (at higher force), we term it slip-ideal bonding.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations